1996
DOI: 10.1089/dna.1996.15.9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Chromosomal Localization of a New Protein Disulfide Isomerase, PDIp, Highly Expressed in Human Pancreas

Abstract: Protein disulfide isomerase (PDI) catalyzes protein folding and thiol-disulfide interchange reactions. The enzyme is localized in the lumen of endoplasmic reticulum (ER) and is abundant in secretory cells of various tissues. In this study we describe the isolation and characterization from human pancreas of a new protein, PDIp, that is structurally and functionally related to PDIs. PDIp cDNA is 1,659 bp in length and predicts a protein with an open reading frame of 511 amino acids. PDIp amino acid sequence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 39 publications
3
73
0
3
Order By: Relevance
“…The same appears to be true for metazoan organisms, in which expression of PDIs also appears to be constitutive, although the actual levels may be higher during fetal development, when large amounts of proteins are being synthesized (42). A pancreas-specific PDI family member appears to be the sole example of a tissue-specific form in adults (43). Thus, the finding of two developmentally regulated PDIs in T. brucei contrasts with the consensus view in the literature that PDIs are constitutively expressed in eukaryotic organisms because of their essential role in protein folding.…”
Section: Discussionmentioning
confidence: 82%
“…The same appears to be true for metazoan organisms, in which expression of PDIs also appears to be constitutive, although the actual levels may be higher during fetal development, when large amounts of proteins are being synthesized (42). A pancreas-specific PDI family member appears to be the sole example of a tissue-specific form in adults (43). Thus, the finding of two developmentally regulated PDIs in T. brucei contrasts with the consensus view in the literature that PDIs are constitutively expressed in eukaryotic organisms because of their essential role in protein folding.…”
Section: Discussionmentioning
confidence: 82%
“…The PDI family member PDIp is exclusively expressed in the pancreas (19) and PDILT, in testis (20). As a lymphocytespecific protein, pERp1 likely is under control of a transcription factor specific for lymphocyte lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about islet expression of PDI, a pancreatic isoform of this protein has been identified (71). Recent studies have shown that NO can react with PDI to inhibit platelet aggregation (72) and that PDI is involved in the entry of NO into cells (73).…”
Section: Discussionmentioning
confidence: 99%